Innovative newborn health technology for resource‐limited environments. Issue 1 (24th December 2012) - Thairu, L.; Wirth, M.; Lunze, K.
Abstract Objectives To review medical devices addressing newborn health in resource‐poor settings, and to identify existing and potential barriers to their actual and efficient use in these settings. Methods We searched Pubmed as our principal electronic reference library and dedicated databases such as Maternova and the Maternal and Neonatal Directed Assessment of Technology. We also researched standard public search engines. Studies and grey literature reports describing devices for use in a low‐ or middle‐income country context were eligible for inclusion. Results Few devices are currently described in the peer‐reviewed medical or public health literature. The majority of newborn‐specific devices were found in the grey literature. Most sources described infant warmers, neonatal resuscitators, and phototherapy devices. Other devices address the diagnosis of infectious diseases, monitoring of oxygen saturation, assisted ventilation, prevention of mother‐to‐child transmission of HIV, assisted childbirth, weight or temperature assessment, and others. Conclusion Many medical devices designed for newborns in the developing world are under development or in the early stages of production, but the vast majority of them are not available when and where they are needed. Making them available to mothers, newborns, and birth attendants in resource‐limited countries at the time and place of birth will require innovative and creative production, distribution, and implementation approaches.